Sustainability in Education: Exploring Teachers' Confidence in Establishing an Out-of-School Learning Environment - Costu, Fatma; Karakus, Neslihan (MDPI, 2025)
Outdoor learning offers dynamic, real-world educational opportunities that extend beyond traditional classrooms and foster sustainability awareness. This quantitative study endeavors to assess teachers' competency in facilitating outdoor learning, aiming for a more engaging and impactful introduction. Employing a relational survey design in the form of a multi-survey model, the research engaged 586 teachers representing diverse academic disciplines across public and private elementary and secondary schools. Central to the investigation was the utilization of the Outdoor Learning Regulation Scale [OLRS] as the primary data collection instrument. The evaluation of teachers' aptitude in regulating outdoor learning encompassed various variables, including gender, subject specialization, prior online or in-person training in outdoor learning, use of non-school environments for teaching, childhood environment, and teaching location. To analyze the collected data, a nuanced approach to statistical analysis was undertaken, aiming to provide a clearer and more specific explanation of the data analysis methods employed. The findings of the study unveiled no significant disparities in teachers' outdoor learning regulation capabilities based on gender, subject specialization, childhood environment, or teaching location. However, discernible differences surfaced in their proficiency in outdoor learning regulation concerning previous online or in-person training in outdoor learning and their utilization of outdoor environments for teaching, thus providing deeper insights into the factors shaping teachers' efficacy in facilitating outdoor learning experiences. Additionally, the study emphasizes the link between outdoor learning and sustainability education. By equipping teachers with the skills to regulate outdoor learning, this research supports the integration of sustainability into educational practices, promoting students' ecological awareness and sustainable thinking. These results highlight the importance of professional development and targeted training in outdoor education, with direct implications for strengthening sustainability-oriented teaching practices.
Keywords: out of school; outdoor learning; sustainability; teacher education; OUTDOOR EDUCATION; EXPERIENCES; Science & Technology - Other Topics; Environmental Sciences & Ecology